DEVELOPING THE FOUR ARABIC LANGUAGE SKILLS AND THEIR ROLE IN ENHANCING COMMUNICATIVE COMPETENCE AMONG NON-NATIVE LEARNERS - Damsing, Nursyuhadah; Che Haron, Sueraya (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
This study investigates methods for developing the four fundamental Arabic language skills - listening, speaking, reading, and writing - and their role in enhancing communicative competence among non-native Arabic learners. Despite years of formal instruction, many learners continue to experience difficulties in using Arabic effectively for real-life communication, particularly due to fragmented skill instruction and limited emphasis on communicative practice. This gap highlights the need for instructional approaches that integrate language skills in a meaningful and communicative manner. The purpose of this study is to identify effective teaching strategies that support the development of communicative competence through the integrated acquisition of the four language skills. A descriptive qualitative approach was employed through a systematic literature review of academic journals, books, and previous research related to Arabic language education. The findings reveal that the integrated development of the four language skills significantly improves learners’ fluency, confidence, and accuracy in communication. Listening and speaking activities play a particularly crucial role in fostering real-time communicative ability while reading and writing contribute to vocabulary development and structural accuracy. The study concludes that effective Arabic language instruction should adopt an integrated, communicative, and learner-centred approach, as this approach directly addresses learners’ communicative challenges and enhances their ability to use Arabic meaningfully in authentic communication contexts.